The road to Paris: Towards a fair and effective climate agreement? - Christiane Reif; Oliver Schenker (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The research conducted at the Research Department "Environmental and Resource Economics, Environmental Management" at ZEW provides a better understanding of environmental policy instruments, national sensitivities, and strategies for overcoming the impediments to global climate policy. The findings of this research can be subsumed by the following key messages: Even in situations of uncertainty, early and credible commitments like "intended nationally determined contributions" (INDCs) serve as important signals for future climate cooperation (Dannenberg et al. 2015). Given that situations and needs vary among countries, discussions on minimum participation rules can be expected to remain controversial among key players (Kesternich forthcoming). Coordinated emission reductions through the linking of different emission trading systems reduce the price tag of global climate policy goals (Hübler et al. 2014). Funding from industrialised countries for adaptation measures in developing countries - a potentially important part of a fair and effective global climate agreement - can be driven by the funders' own self-interest and motivated by international trade (Schenker and Stephan 2014).
Keywords: 330